Dialogic model of conflict prevention (Journal of Parents and Teachers, 2016)
This article discusses key information that allows to know and apply the dialogic model of conflict prevention. Through the description of this successful educational action, we will see how the dialogue of all stakeholders in a learning community can contribute to overcome risk situations and conflicts that should never be allowed in a school.
Keywords: Dialogic model of conflict prevention; breaking the silence; norm; coexistence.